THE RELATIONSHIP BETWEEN READING ATTITUDE AND READING COMPREHENSION OF VOCATIONAL STUDENTS - Sri Purwaningsih; Desi Surlitasari Dewi; Eka Wilany (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this research is to find out whether there is a significant correlation between students’ reading attitude and students’ reading comprehension of eleventh grade students of SMKS Hidayatullah Batam in the academic years 2020/2021. Students who have low reading attitude have low reading comprehension. The data of the research were taken from a reading attitude scale to obtain data about students’ reading attitude and the TOEIC reading test to obtain data about students’ reading comprehension. The population were 50 students of eleventh grade students of SMKS Hidayatullah Batam in the academic years 2020/2021. The sample were taken from 24 samples of research data selected by using cluster random sampling. Before testing the hypothesis, the researcher conducted a normality test by using Shapiro-Wilk test. The data of students’ reading attitude has a significance value of 0.080 and a significance value of students’ reading comprehension was 0.112 is bigger than 0.05. After the normality test was carried out, the researcher conducted the hypothesis testing by using Pearson Product Moment. The research data showed that the rcount (-0.160) is lower tha rtable (0.404). based on the result of the research data, it can be concluded that there was no significance correlation between students’ reading attitude and students’ reading comprehension of eleventh grade students of SMKS Hidayatullah Batam in the academic years 2020/2021.